(untitled) (TAMADDUN NURI JURNALI, 2024)
While studying the pedagogical views of Sulayman Bakirghani, he promoted the Islamic religion, Sharia and Tariqat rules in his wisdom. In his teachings, Sulayman Bakirghani tries to remind people of the horror of the sufferings of the world and educate those who are responsible for the inequality, injustice and other evils of the people of his time in social life. He exposes dishonest and unbelieving officials, people who do bad things, scoundrels, ignorant and ignorant people, as well as raiders and robbers.